Analysis On Students' Difficulties In Reading Comprehension Report Text - Anisa Sapitri; Lis Supiatman; Susi Masniari Nasution (JURNAL GLOBAL EDUKASI, 2022)
Abstract: This research was conducted to analyze the most dominant difficulties and the factors causes students difficulty in reading comprehension. The objective of this research is to identify the difficulties faced by the eleventh grade students of SMA  Swasta  Islam  Terpadu  Daar  Al  Uluum Kisaran, to  identify  factors  of causing the students difficulties in reading comprehension at the eleventh grade students SMA Swasta Islam Terpadu Daar  Al Uluum Kisaran 2020/2021 Academic  Year.  This  research  is  a  qualitative  research.  The  subject  of  this research was the eleventh grade students of SMA Swasta Islam Terpadu Daar Al Uluum Kisaran 2020/2021 Academic Year. The techniques of collecting the data are Test and Interview. The researcher used the technique of analyzing the data from Miles and Huberman. The factor of causing the students difficulties found in difficulties reading comprehension there are difficulty in understanding vocabulary, house environment, school environment and the lack of students in learning English. Keywords: environment; reading; vocabulary  Abstrak: Penelitian ini dilakukan untuk menganalisis kesulitan yang paling dominan dan faktor penyebab kesulitan siswa dalam membaca pemahaman. Tujuan dari penelitian ini adalah untuk mengidentifikasi kesulitan-kesulitan yang dihadapi siswa kelas XI SMA Swasta Islam Terpadu Daar Al Uluum Kisaran, mengidentifikasi faktor-faktor penyebab kesulitan siswa dalam membaca pemahaman siswa kelas XI SMA Swasta Islam Terpadu Daar Al Uluum Kisaran. Tahun Pelajaran 2020/2021. Penelitian ini merupakan penelitian kualitatif. Subjek penelitian ini adalah siswa kelas XI SMA Swasta Islam Terpadu Daar Al Uluum Kisaran Tahun Pelajaran 2020/2021. Teknik pengumpulan datanya adalah Tes dan Wawancara. Peneliti menggunakan teknik analisis data dari Miles dan Huberman. Faktor penyebab kesulitan siswa yang ditemukan dalam kesulitan membaca pemahaman yaitu kesulitan dalam memahami kosakata, lingkungan rumah, lingkungan sekolah dan kurangnya siswa dalam belajar bahasa Inggris. Kata kunci: kosa kata; lingkungan; membaca